2009
DOI: 10.1103/physreve.79.036203
|View full text |Cite
|
Sign up to set email alerts
|

Origin of chaos near critical points of quantum flow

Abstract: The general theory of motion in the vicinity of a moving quantum nodal point (vortex) is studied in the framework of the de Broglie-Bohm trajectory method of quantum mechanics. Using an adiabatic approximation, we find that near any nodal point of an arbitrary wave function psi there is an unstable point (called the X point) in a frame of reference moving with the nodal point. The local phase portrait forms always a characteristic pattern called the "nodal-point- X -point complex." We find general formulas for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(146 citation statements)
references
References 50 publications
6
128
0
12
Order By: Relevance
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 61%
“…In a series of works published later on by Wisniacki and coworkers [282,283] it was shown that the origin of Bohmian chaos is in the evolution in time of those vortices. An analogous conclusion was also found by Efthymiopoulos and coworkers [197,[284][285][286][287], who showed that chaos is due to the presence of moving quantum vortices forming nodal point-X-point complexes. In particular, in reference [197] a theoretical analysis of the dependence of Lyapunov exponents of Bohmian trajectories on the size and speed of the quantum vortices is presented, which explains their earlier numerical findings [284,285].…”
Section: Role Of Vortical Dynamicssupporting
confidence: 61%
“…The de Broglie -Bohm theory, also called the pilot-wave theory or the quantum theory of motion, is an interpretation of quantum theory which has attracted the attention of researchers in recent years [1,2,15,[17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In their review of 100 years of quantum physics when celebrating the first hundred years of quantum physics, Tegmark and Wheeler considered Bohmian mechanics one of the most significant elements in its history [27].…”
Section: Preliminariesmentioning
confidence: 99%
“…In their review of 100 years of quantum physics when celebrating the first hundred years of quantum physics, Tegmark and Wheeler considered Bohmian mechanics one of the most significant elements in its history [27]. Among the fascinating facets of Bohm's theory one can mention its relevance for the study of quantum chaos [32] and for the quantum measurement problem [1,2,19], and its applications to quantum cosmology [28][29][30][31]. Thermal equilibrium of quantum systems [34], entanglement [33], and the dynamics of quantum particles with position-dependent effective mass [35] have also been recently considered within Bohm's approach.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations